The Sharī’ah position on human embryonic research - Zawawi, Majdah; Alias, Siti Aliza; Hussin, Nasimah (The Malaysian Current Law Journal Sdn Bhd, 2016)
The quest for medical advancement has resulted in breakthroughs being made in the area of biomedical science. Scientist are now able to work with human embryos left over from assisted reproductive treatments of infertile couples in order to explore various therapeutic possibilities. Not only that, the creation of embryos solely for research purposes is also possible through somatic cell nuclear transplantation techniques (SCNT).